Global research on endocrine disruptors as emerging hazards for human health and the environment - Klingelhöfer, Doris; Braun, Markus; Dröge, Janis; Brüggmann, Dörthe; Groneberg, David A. (Frontiers in Endocrinology, 2025)
Endocrine disruptors (EDs) contaminate nearly every ecosystem and are significantly associated with different neurological and neurodevelopmental disorders. To date, there is no comprehensive literature on global publication efforts. Since there are many unknown substances, modes of action, and risks of EDs, it is necessary to provide detailed insight into global publication patterns from temporal, regional, and socioeconomic perspectives. Hence, this review article provides background information for all stakeholders, from scientists to clinicians and policymakers. A disproportionate increase in research activity was observed, mainly from the USA and China, with a strong north-south divide. Multi-disciplinarity is characteristic, with a trend toward an ecological focus. Low- and middle-income economies are underrepresented in research on EDs. Therefore, global research needs to be refocused and expanded to more global approaches that take inspiration from the few successful collaborations with their synergistic effects.